Contact sensitivity to oak moss - Gonçalo, S (2012)
Oak moss allergy was the principle allergen in contact sensitivity to perfumes (45%); 31 patients reacting to oak moss were studied. The sensitivity was attributed to contact with perfumes in 20, lichens in 7 and unknown in 4. Atranorin was the most frequent allergen, followed by usnic, evernic and fumarprotocetraric acids. Concomitant allergy occurred to several lichen acids and also to balsam of Peru, colophony and other fragrance components.